DLS dynamic backlight luminance scaling of liquid crystal display. - Naehyuck Chang (IEEE Transactions on VLSI systems)
Backlight systems dominate the power requirements of battery-operated hand-held devices with color thin-film transistor (TFT), liquid crystal displays (LCDs). We introduce dynamic luminance scaling of the backlight with appropriate image compensation. Dynamic backlight luminance scaling (DLS) keeps the perceived intensity or contrast of the image as close as possible to the original while achieving significant power reduction. DLS compromises quality of image between power consumption, which fulfills a large variety of user preferences in power-aware multimedia applications. DLS saves 20% to 80% of power consumption of the backlight systems while keeping a reasonable amount of image quality degradation.